Traumatic spinal injuries in Saudi Arabia: a retrospective single-centre medical record review - Alawad, Mohammad O (BMJ Open, 2020)
OBJECTIVES: To describe the patterns and outcomes of traumatic spinal injuries (TSIs) in a tertiary care trauma centre in Riyadh, Saudi Arabia. DESIGN: Retrospective medical record review. SETTING: Level 1 trauma centre for all patients presented from 1 February 2016 to 31 December 2018. PARTICIPANTS AND DATA: Records of patients presenting with any spinal trauma were reviewed, and the data obtained included age, gender, nationality (as Saudi and non-Saudi), date of presentation, site of fracture/injury, associated injuries, mechanism of injury, presence of neurological involvement and hospital mortality. MAIN OUTCOMES: Frequencies of different types of TSI across various subgroups. RESULTS: We identified 692 patients who presented with TSI throughout the study period. The mean age was 36.9 years. Males represented 83.2% (n=576) of the sample size, and the most common mechanism of injury was motor vehicle collision (MVC), accounting for 66.8% of cases (n=462), while fall-related injuries were seen in 31.6% of cases (n=219). A total of 454 (65.6%) of all patients were Saudi, and 332 (73.1%) of the TSIs in Saudis were due to MVC. Non-Saudi cases accounted for 238 (34.4%) of all patients, and 89 (37.4%) of the non-Saudi injuries were due to falls from height, and this association was statistically significant (p<0.001). CONCLUSION: TSI was not thoroughly examined in Saudi Arabia; therefore, this study is considered the first to be done in the Kingdom using a representative sample. The fact that non-Saudi patients had a higher proportion of falls as a mechanism of injury should be taken into consideration in terms of raising awareness and taking more safety precautions, as most construction workers tend to be expatriates.